2009
DOI: 10.1007/s00405-009-0963-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of caspofungin and voriconazole in an experimental fungal infection of the ear due to Aspergillus

Abstract: The purpose of the study was to evaluate the effectiveness of caspofungin and voriconazole in the treatment of experimental Aspergillus otitis media in an experimental rabbit model. A total of 30 New Zealand white rabbits were divided into four treatment groups and one control group. The rabbits were immunosuppressed by cyclophosphamide and triamcinolone acetonide. The right ear of each rabbit was infected by an injection of the inoculum of 0.1 ml (8.6 x 103 CFU/0.1 ml) of Aspergillus fumigatus into the middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In an in vitro study conducted by Erbek et al [20] it was reported that both agents showed the same activity rate (97.8%) as amphotericin B against the fungi tested. When assessed with clinical, microbiological, and histopathological techniques, caspofungin and voriconazole were shown to be as effective as amphotericin B and itraconazole, which were considered the standard regimens towards the treatment of fungal infections of the ear [6]. Voriconazole is currently considered as the first line therapeutic option for invasive aspergillosis, based on its high intrinsic anti- Aspergillus activity [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an in vitro study conducted by Erbek et al [20] it was reported that both agents showed the same activity rate (97.8%) as amphotericin B against the fungi tested. When assessed with clinical, microbiological, and histopathological techniques, caspofungin and voriconazole were shown to be as effective as amphotericin B and itraconazole, which were considered the standard regimens towards the treatment of fungal infections of the ear [6]. Voriconazole is currently considered as the first line therapeutic option for invasive aspergillosis, based on its high intrinsic anti- Aspergillus activity [7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recommended as the primary therapy for acute invasive aspergillosis in international guidelines [2]. Additionally, voriconazole has shown significant activity in patients with central nervous system and bone aspergillosis [6, 7]. Long term treatment with this antifungal agent is well tolerated and it is available for intravenous and oral use [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations